2018
DOI: 10.1021/jacs.7b11056
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Model of a P450-Ferredoxin Complex from Orientation-Selective Double Electron–Electron Resonance Spectroscopy

Abstract: Cytochrome P450 (CYP) monooxygenases catalyze the oxidation of chemically inert carbon-hydrogen bonds in diverse endogenous and exogenous organic compounds by atmospheric oxygen. This C-H bond oxy-functionalization activity has huge potential in biotechnological applications. Class I CYPs receive the two electrons required for oxygen activation from NAD(P)H via a ferredoxin reductase and ferredoxin. The interaction of Class I CYPs with their cognate ferredoxin is specific. In order to reconstitute the activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 90 publications
(155 reference statements)
0
21
0
Order By: Relevance
“…For CYP116 family, two crystal structures of the heme domain have been reported and their substrate-binding modes were proposed accordingly 26,27 . The complex structures of a heme domain and ferredoxin from P450 systems that acquire electrons from separate redox partners have also been reported [28][29][30][31] , which demonstrated how the electrons are injected from [2Fe-2S] cluster to the heme (Supplementary Fig. 2b).…”
mentioning
confidence: 64%
“…For CYP116 family, two crystal structures of the heme domain have been reported and their substrate-binding modes were proposed accordingly 26,27 . The complex structures of a heme domain and ferredoxin from P450 systems that acquire electrons from separate redox partners have also been reported [28][29][30][31] , which demonstrated how the electrons are injected from [2Fe-2S] cluster to the heme (Supplementary Fig. 2b).…”
mentioning
confidence: 64%
“…For the related P450–ferredoxin complexes of CYP199A2‐HaPux (top ranked complex from structure determination by orientation‐selective double electron–electron) and of CYP101A1‐Pdx (pdb entry http://www.rcsb.org/pdb/search/structidSearch.do?structureId=4JWS.pdb) the obtained RMSD values are much higher (14.1 Å and 13.6 Å, respectively). Visual inspection, however, showed that the binding site is matched, but the ferredoxins are somewhat skewed.…”
Section: Resultsmentioning
confidence: 99%
“…The latter case has severala dvantages and applications: 1) the use of metal centers forP DS allows to reduce the number of spin labels and, consequently,t he number of protein mutations, 2) it enables orthogonal spin labeling [8] as the metal center has different spectroscopic properties than the majority of spin labels, 3) the distance constraintso btained from such PDS measurementse nable the localization of metal ions within the protein fold by trilateration [9,10] and the docking of different parts of protein complexes using metal ions as anchor points. [11] To date, PDS measurements have been applied to av ariety of different intrinsic metal centers, such as Cu 2 + , [12][13][14][15][16][17][18][19][20] Mn 2 + , [21][22][23][24][25] Co 2 + , [26,27] and low-spin Fe 3 + , [6,[28][29][30][31] as well as ironsulfur [17,[32][33][34] and manganese [35,36] clusters. In all these cases, the protocols for PSD measurements are well-established and the extractiono fd istance constraints from the corresponding PDS data can be readily achieved under the high-field approximation.…”
Section: Introductionmentioning
confidence: 99%